Brazil - Strategies for Poverty Reduction in Ceara : The Challenge of Inclusive Modernization, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Why is there still severe deprivation in Ceara after so many years of active development eforts? Have government programs been well-designed? What can be done differently in the future? How can a more inclusive strategy be combined with the modernization effort? This report argues that a well-designed redistributive strategy is not only consistent with modernization, but is an important complement. Societies that effectively manage inequality and insecurity typically have deep and broad educational systems, and responsive and inclusive political and institutional structures. These can be sources of competitiveness and resilience in the global economy. But there is no magic solution. Success will depend on a range of complementary actions to tackle the various areas of disadvantage to create a virtuous cycle of change that is both redistributuve and growth-oriented. In particular, the report finds that growth alone will be a weak instrument of poverty decline, precisely because of the extent of inequality. Thus the report proposes complementary efforts in four areas: achieving a more equitable pattern of income and job growth; continuing and deepening the effort to get equitable skills development; use of redistributuve transfers for the poor and indigent, as a means of complementing human capital development; and strengthening institutional change, especially at the municipal level.